The Correlation of Age and Comorbid Diseases to the Risk of Renal Impairment in Tuberculosis Patients at the Prof. Dr. H. Aloei Saboe Regional General Hospital, Gorontalo City - Ahmad Fahrian Hipmi Fahrian (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2025)
Tuberculosis (TB) is a major health problem in Indonesia, including Gorontalo City. Anti-tuberculosis drugs (OAT) are the primary therapy in TB treatment, but the use of OAT can trigger various side effects, such as kidney disorders. This study aims to analyze the side effects of renal impairment from OAT use and the relationship with age and comorbid diseases in TB patients at Prof. Dr. H. Aloei Saboe Hospital. The study employed an analytical observational  approach with a retrospective design, utilizing medical record data collected from 2022 to 2024. Correlation analysis was conducted using the chi-square test . The results showed that the majority were male as many as 251 people (60.77%), the majority of the age group was 55-64 years old, as many as 98 people (23.73%) and most received OAT category 1 treatment for new cases as many as 398 people (96.37%). Diabetes mellitus (DM) comorbidity with 101 patients (24.45%), hypertension comorbidity with 55 patients (13.31%), and renal impairment side effects experienced by 45 patients (10.90%). The correlation between age and renal impairment was significant, at the age of 15-24 years (OR: 0.28; 95% CI: 0.08 - 0.94; p = 0.04), age 45-54 years (OR: 2.12; 95% CI: 1.08-4.16; p = 0.04), and age 35-44 years (OR: 0.13; 95% CI: 0.01-0.97; p = 0.03). The comorbid DM (OR: 2.54; 95% CI: 1.34-4.83; p = 0.00) and hypertension (OR: 2.58; 95% CI: 1.36-4.89; p = 0.00) with renal impairment was significant. In conclusion, age and comorbidities play an important role in determining the adverse effects of renal impairment in TB patients.